Populism in Journalistic Photographs: Political Leaders in Venezuelan Newspaper Images - Virpi Salojarvi (Iberoamericana: Nordic Journal of Latin American and Caribbean Studies, 2019)
Former Venezuelan President Hugo Chávez was renowned for his media skills and public appearances. In this study, his visual media representations are compared to those of other politicians in a framework of populism. The data includes articles by two Venezuelan newspapers representing opposing political views, and is analysed using content analysis and visual rhetorical interpretation. The focus is on the ways in which the sense of belonging, including its affective aspects, are visually constructed in journalistic photographs. It was found that, as a signifier, Chávez was constructed using many different techniques in the government-leaning newspaper. In this way, the image of Chávez was constructed by depicting him as someone special and authentic, distinct from other politicians, powerful yet at one with the people at the same time, and both evincing and generating emotion. The anti-Chávez newspaper, on the other hand, depicted the opposition leader in a more traditional and less emotional way, and despite an arranged photo opportunity, the newspaper was able to put its own slant on the Chavista politicians. The article contributes to the scarce literature of visual aspects of Venezuelan politics under Chávez’s presidency, and understudied affective and performative dimensions of populism.